Portfolio Analysis: Documenting the Progress and Performance of Educational Administration Students.. - Teresa Northern Miller; Trudy Salsberry (Educational Considerations, 2005)
The field of educational administration continues to evolve as practitioners and researchers face the challenges of preparing leaders for schools.